Pengaruh Perencanaan Karir dan Pengembangan Karir Terhadap Motivasi Kerja Pegawai: (Studi pada Pegawai Bank Bjb Sindangkasih Kabupaten Ciamis) - Sidna Anggia Pravitadewi; Ading Rahman Sukmara; Luffi Septian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is motivated by the low motivation of employees in carrying out their main tasks and functions. This can be seen from the lack of enthusiasm of employees in carrying out their duties and the lack of obsession to progress. This low employee motivation is thought to be caused by two factors, namely, less than optimal career planning and the unclear arrangement of career development for employees who are considered to have achieved. The purpose of this study is to determine how career planning affects employee work motivation, how career development affects employee work motivation, and how career planning and development together affect employee work motivation. The method used in this study uses a quantitative descriptive method. To analyze it, correlation and multiple regression statistical test data analysis was used using SPSS version 22.00. The results of the study obtained provide the conclusion that career planning has a positive and significant effect on employee work motivation, career development has a positive and significant effect on employee work motivation, and career planning and career development have a positive and significant effect on employee work motivation.